Higher TIER bumble bees and solitary bees recommendations for a semi-field experimental design - Allan, Matthew J.; Alscher, Annika; Amsel, Kristin; Classen, Christian; Cornement, Magdaléna; Elston, Charlotte; Exeler, Nina; Franke, Lea; Frommberger, Malte; Giffard, Hervé; Guerola, Juan Sorlí; Hecht-Rost, Sabine; et al. (Julius-Kühn-Archiv, 2020)
The publication of the proposed EFSA risk assessment guidance document of plant protection products for pollinators highlighted that there are no study designs for non-Apis pollinators available. Since no official guidelines exist for semi-field testing at present, protocols were proposed by the ICPPR non-Apis working group and two years of ring-testing were conducted in 2016 and 2017 to develop a general test set-up. The ringtest design was based on the draft EFSA guidance document, OEPP/EPPO Guideline No. 170 and results of discussions regarding testing solitary bees and bumble bees during the meetings of the ICPPR non-Apis workgroup. Ring-tests were conducted with two different test organisms, one representative of a social bumble bee species (Bombus terrestris L; Hymenoptera, Apidae) and one representative of a solitary bee species (Osmia bicornis L; Hymenoptera, Megachilidae). The species are common species in Europe, commercially available and widely used for pollination services. Several laboratories participated in the higher-tier ring tests. 15 semi-field tests were conducted with bumble bees and 16 semi-field tests were done with solitary bees in 2016 and 2017. Two treatment groups were always included in the ringtests: an untreated control (water treated) and the treatment with dimethoate as a toxic reference item (optional other i.e. brood-affecting substances fenoxycarb or diflubenzuron). The toxic reference items were chosen based on their mode of action and long term experience in honey bee testing. A summary of the ringtest results will be given and the recommendations for the two semi-field test designs will be presented.